Characteristics and determinants of Thailand's declining birth rate in women age 35 to 59 years old: Data from the fourth national health examination survey - Kriengkrai Correction Srithanaviboonchai (2018)
Objective: To describe characteristics and determinants of Thailand's declining birth rate using national representative survey data. Material and Method: The Fourth National Health Examination Survey was conducted between 2008 and 2009. Four stages of stratified probability samples, proportionate to size, were used to represent the whole Thai population. Information from women aged 35 to 59 years old was included in the analysis. Curve estimation was used to characterize the correlation between the number of children ever born and the age of married and un-married women. Binary logistic regression analysis was used to identify predictors of having fewer than two children among ever married women. Results: Of all 4120 women, the number of children decreased sharply among the oldest women aged 45 to 59 years old, decreased less sharply for women younger than 45 years of age, reached the lowest level at the age of 37 and 38 years old, and then increased minimally among the younger women surveyed. Among those who were ever married (n = 3,761), the independent predictors of having one or no child instead of having two or more children were aged 45 to 49 compared to 50 to 59 years old (OR = 1.66; 95% CI = 1.37-2.00), age 35 to 44 compared to 50 to 59 years old (OR = 1.39; 95% CI = 1.16-1.68), living in households with wealth index level 3 compared to level 1 (OR = 1.28; 95% CI = 1.01-1.63), urban residence (OR = 1.33; 95% CI = 1.14-1.57), attaining secondary school education (OR = 1.35; 95% CI = 1.11-1.64), and having junior college diploma or higher level of education compared to elementary or no education (OR = 1.81; 95% CI = 1.39-2.34). Conclusion: Birth rate of Thai women declined steeply in the past then less steeply, and might have begun to rise minimally in recent years. Younger age, living in an urban area, and having higher socioeconomic status were predictors of having fewer than two children.